2012
DOI: 10.1021/ja301328f
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Flexible β-Strands into Immobile Amyloid-Like β-Sheets in Membranes As Revealed by Solid-State 19F NMR

Abstract: The cationic peptide [KIGAKI](3) was designed as an amphiphilic β-strand and serves as a model for β-sheet aggregation in membranes. Here, we have characterized its molecular conformation, membrane alignment, and dynamic behavior using solid-state (19)F NMR. A detailed structure analysis of selectively (19)F-labeled peptides was carried out in oriented DMPC bilayers. It showed a concentration-dependent transition from monomeric β-strands to oligomeric β-sheets. In both states, the rigid (19)F-labeled side chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 30 publications
3
101
0
Order By: Relevance
“…Impacts of peptide self-assembly on peptide-cell interaction have been revealed in recent publications 21, 30 . Results from this study suggest that peptide aggregation could be as important as the charge and secondary structure of a peptide in affecting peptide-cell interactions.…”
Section: Discussionmentioning
confidence: 98%
“…Impacts of peptide self-assembly on peptide-cell interaction have been revealed in recent publications 21, 30 . Results from this study suggest that peptide aggregation could be as important as the charge and secondary structure of a peptide in affecting peptide-cell interactions.…”
Section: Discussionmentioning
confidence: 98%
“…OCD is a powerful tool for studying the orientation of membrane-active peptides and protein segments in membranes (Lange et al, 2007;Bürck et al, 2008;Strandberg et al, 2008;Wadhwani et al, 2008Wadhwani et al, , 2012Wadhwani et al, , 2014Nolandt et al, 2009;Windisch et al, 2010;Heinzmann et al, 2011;Klein et al, 2012;Muhle-Goll et al, 2012;Steinbrecher et al, 2012;Aberle et al, 2014;Fanghänel et al, 2014). For α-helices, the OCD band at 208 nm can be used to estimate the helix tilt angle relative to the membrane normal (Wu et al, 1990).…”
Section: Orientation Of E5 In the Membrane By Ocdmentioning
confidence: 99%
“…Three different models for peptidemembrane interaction are commonly used: barrel-stave, toroidal and carpet models [9][10][11]. It was suggested that collective behaviour of peptides can play a role in the bacterial membrane destruction [12][13][14][15][16][17][18][19]. For instance, using 31 P oriented solid-state NMR experiments it was found that at high peptide concentration alamethicin adopts a transmembrane conformation while the novicidin forms a toroidal pore in the membrane [16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using 31 P oriented solid-state NMR experiments it was found that at high peptide concentration alamethicin adopts a transmembrane conformation while the novicidin forms a toroidal pore in the membrane [16]. Using solid-state 19 F NMR it was shown that at low concentration the amphiphilic [KIGAKI] 3 peptide binds to membrane as flexible β-strand, without forming any intra or intermolecular Hbonds [13]. At higher concentrations [KIGAKI] 3 self-assembles into immobilized β-sheets which lie flat on the membrane surface as amyloid-like fibrils.…”
Section: Introductionmentioning
confidence: 99%